Flexible starch-polyurethane films: Effect of mixed macrodiol polyurethane ionomers on physicochemical characteristics and hydrophobicity. (1st October 2018) - Tai, N.L.; Adhikari, Raju; Shanks, Robert; Halley, Peter; Adhikari, Benu
Highlights: Films were produced by blending anionic poly(ether-ester)urethane (AEEPU) and starch. Molecular entanglement and hydrogen bonding occurred between starch & AEEPU. Miscibility and compatibility between starch & AEEPU were significantly high. Flexibility, hydrophobicity and transparency of these films were close to that of LDPE. Starch-AEEPU films can be used in packaging applications as an alternative of LDPE. Abstract: One of the most critical limitations in synthesizing starch-polyurethane (PU) hybrid materials is their microphase separation caused by physical incompatibility. This paper reports that the physical incompatibility and microphase separation between starch and PU can be overcome by using specifically designed anionic poly(ether-ester) polyurethane (AEEPU). The AEEPU was synthesised by preparing isocyanate (NCO)-terminated prepolymer using Isophorone diisocyanate (IPDI), 2, 2-bis(hydroxymethyl)propionic acid (BMPA), poly (ethylene glycol) (PEG) and polycaprolactone (PCL). This AEEPU was physically mixed with glycerol plasticized high amylose starch (HAGS) at HAGS to AEEPU mass ratios of 90/10, 80/20, 70/30, 60/40, 50/50. Higher AEEPU content in HAGS-AEEPU increased surface hydrophobicity and elasticity while the Young's modulus remained unaffected. HAGS-AEEPU film at 50:50 ratio was comparable to LDPE film in terms of elongation at break (187%), Young's modulus (383 MPa), and contact angle (112°) and good transparency. These starch-PU films are expected to find increased application as biodegradable packaging materials.